2015
DOI: 10.1186/s12871-015-0144-3
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol pharmacokinetics and metabolism in young women

Abstract: BackgroundThere is relevant between individual variability in paracetamol clearance in young women. In this pooled study, we focused on the population pharmacokinetic profile of intravenous paracetamol metabolism and its covariates in young women.MethodsPopulation PK parameters using non-linear mixed effect modelling were estimated in a pooled dataset of plasma and urine PK studies in 69 young women [47 at delivery, 8/47 again 10–15 weeks after delivery (early postpartum), and 7/8 again 1 year after delivery (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…In brief, first, a PBPK model was previously developed for both intravenous and oral acetaminophen administration in non-pregnant women. The predictive performance of the model was evaluated by comparing simulations with observed in vivo pharmacokinetic profiles of acetaminophen, acetaminophen-glucuronide, acetaminophen-sulphate, and unchanged acetaminophen after both oral and intravenous acetaminophen administration of standard dosages [20][21][22]. Once the non-pregnant PBPK model captured the observed pharmacokinetics adequately, all drug-specific parameters were fixed and pregnancy-specific changes were incorporated.…”
Section: Development Of Fetal-maternal Physiologically Based Pharmacomentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, first, a PBPK model was previously developed for both intravenous and oral acetaminophen administration in non-pregnant women. The predictive performance of the model was evaluated by comparing simulations with observed in vivo pharmacokinetic profiles of acetaminophen, acetaminophen-glucuronide, acetaminophen-sulphate, and unchanged acetaminophen after both oral and intravenous acetaminophen administration of standard dosages [20][21][22]. Once the non-pregnant PBPK model captured the observed pharmacokinetics adequately, all drug-specific parameters were fixed and pregnancy-specific changes were incorporated.…”
Section: Development Of Fetal-maternal Physiologically Based Pharmacomentioning
confidence: 99%
“…Once the non-pregnant PBPK model captured the observed pharmacokinetics adequately, all drug-specific parameters were fixed and pregnancy-specific changes were incorporated. Model performance was evaluated by comparing simulations with observed in vivo pharmacokinetic profiles of acetaminophen, acetaminophenglucuronide, acetaminophen-sulphate, and unchanged acetaminophen obtained from third-trimester pregnant women [20]. For more detailed information about parameterization and validation of the previously developed pregnancy PBPK model we refer to Mian et al [17].…”
Section: Development Of Fetal-maternal Physiologically Based Pharmacomentioning
confidence: 99%
“…Regarding the plasma concentration-time profiles of oral acetaminophen 1000 mg in non-pregnant and pregnant populations (ESM_2A), maximum concentration (C max ) values were higher in non-pregnant women and decreased with increasing duration of gestational week, while the AUC from time zero to 6 h (AUC 0-6h ) decreased with increasing duration of gestational age. Regarding the plasma concentration-time profiles of NAPQI after administration of oral [31] acetaminophen plasma concentration-time profiles (left) and predicted and observed [31] acetaminophen inactive metabolites urine concentration-time profiles (right) in populations of a non-pregnant women after administration of intravenous acetaminophen 2000 mg and b third trimester pregnant women after administration of an intravenous acetaminophen 2000 mg loading dose followed by 1000 mg every 6 h. For the inactive metabolites, orange, pink, and green indicate acetaminophen glucuronide, acetaminophen sulfate, and unchanged acetaminophen in urine concentrations, respectively. The shaded area denotes the predicted 95% confidence interval.…”
Section: Pbpk Models For Acetaminophenmentioning
confidence: 99%
“…Following oral administration of acetaminophen 1000 mg, the predicted C ss,avg (median [interquartile range, IQR]) was 6.7 Goodness-of-fit plot (predicted concentration versus observed concentration) for acetaminophen and its metabolites (acetaminophen unchanged, acetaminophen glucuronide, acetaminophen sulfate). For non-pregnant women, observed acetaminophen data were taken from Allegaert et al [31], Mitchell et al [34], and Beaulac-Baillargeon and Rocheleau [33]; for pregnant women, observed acetaminophen, acetaminophen glucuronide, and acetaminophen sulfate data were taken from Allegaert et al [31] and Beaulac-Baillargeon and Rocheleau [33]. The solid line denotes the line of identity.…”
Section: Acetaminophen Average Concentration At Steady State and Acetmentioning
confidence: 99%
See 1 more Smart Citation